2003
DOI: 10.1007/bf03345138
|View full text |Cite
|
Sign up to set email alerts
|

GH release after GHRH plus arginine administration in obese and overweight women with polycystic ovary syndrome

Abstract: Few and unclear data are available in the literature about the relationship between impairment of GH/IGF-I axis and polycystic ovary syndrome (PCOS). This study was aimed to evaluate the basal GH and IGF- levels, and GH release after challenge test in obese and overweight women with PCOS. Thirty patients with PCOS and other 30 healthy women matched for age, body mass index (BMI) and waist-hip ratio (WHR) were studied. Serum follicle-stimulating hormone (FSH), LH, PRL, E2, P, 17OH-progesterone (17OH-P), total T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…High insulin levels have been shown to decrease levels of IGFBP-1, and this may elevate serum levels of free IGF-I and subsequently inhibit the secretion of GH through increased IGF-I feedback on the pituitary (17). In agreement with this hypothesis, several studies found significantly higher levels of serum total IGF-I in PCOS patients, compared with weight-matched controls (5,(42)(43)(44); however, other studies were not able to reproduce this. As recently reviewed by Frystyk (17), measurement of free IGF-I may be a better indicator of the GH secretion in conditions with an abnormal insulin sensitivity.…”
Section: Discussionmentioning
confidence: 66%
“…High insulin levels have been shown to decrease levels of IGFBP-1, and this may elevate serum levels of free IGF-I and subsequently inhibit the secretion of GH through increased IGF-I feedback on the pituitary (17). In agreement with this hypothesis, several studies found significantly higher levels of serum total IGF-I in PCOS patients, compared with weight-matched controls (5,(42)(43)(44); however, other studies were not able to reproduce this. As recently reviewed by Frystyk (17), measurement of free IGF-I may be a better indicator of the GH secretion in conditions with an abnormal insulin sensitivity.…”
Section: Discussionmentioning
confidence: 66%
“…A significantly lower GH response to exercise was demonstrated in patients with PCOS, with a negative correlation between GH response and BMI (34). Both the mean peak value of GH and the total GH response to GHRH plus arginine were found to be significantly lower in obese patients with PCOS than in healthy obese women (35). Obese women with PCOS show a markedly decreased GH response to the administration of GHRH (14) in basal conditions.…”
Section: Discussionmentioning
confidence: 97%